2017
DOI: 10.1590/s1677-5538.ibju.2016.0315
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcomes in partial nephrectomy: is the renal score useful?

Abstract: Introduction and Objective The R.E.N.A.L. nephrometry system (RNS) has been validated in multiple open, laparoscopic and robotic partial nephrectomy series. The aim of this study was to test the accuracy of R.E.N.A.L. nephrometry system in predicting perioperative outcomes in surgical treatment of kidney tumors <7.0cm in a prospective model.Materials and Methods Seventy-one patients were selected and included in this prospective study. We evaluate the accuracy of RNS in predicting perioperative outcomes (WIT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…This was in the range of reported complications in other studies (24.24-38.46%) [2,13,[23][24][25][26]. We had 4 cases (7.8%) of conversion to RN which was similar to that found in different studies (6-16.3%) [17,27,28].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This was in the range of reported complications in other studies (24.24-38.46%) [2,13,[23][24][25][26]. We had 4 cases (7.8%) of conversion to RN which was similar to that found in different studies (6-16.3%) [17,27,28].…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, the new score is ranging from 5 to 23. It is classified into mild complexity (5)(6)(7)(8)(9), moderate complexity (10)(11)(12)(13)(14) or high complexity (15)(16)(17)(18)(19)(20)(21)(22)(23). A renal mass can be described using the MNS as (R + E + N + ap x + L + H + RPS).…”
Section: Newly Modified Nephrometry Score (Mns)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed comparable PSM rates for central and peripheral tumors [51], others a higher risk for central located tumors [52,53]. In the last years, some studies stratified PSM rates according to the risk categories defined by nephrometry scores [8,16,34]. No study demonstrated a significant impact of nephrometry score on risk of PSMs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] A prospective study performed by Matos et al ., which included 71 patients, showed that the RNS was a good method in predicting surgical access route and type of nephrectomy, and the RNS was also associated with OT and WIT, but with weak accuracy. [ 20 ] Kriegmair et al . conducted a systemic comparison of the aforementioned nephrometry scoring systems and concluded that all scoring systems represent objective and reproducible measurement tools for renal tumor complexity, and that the RENAL, PADUA, and NePhRO scores are comparable and seem to be more superior to C-index.…”
Section: Discussionmentioning
confidence: 99%